Mecanismos de governança e geração de ganhos relacionais: uma análise em cadeias de suprimentos de alimentos orgânicos - Cislaghi, Tatiane Pellin (Universidade do Vale do Rio dos Sinos, 2019)
Interorganizational relationships in the supply chains context are influenced by governance mechanisms and contextual factors related to the environment in which organizations are embedded. The purpose of this study is to analyze how the use of governance mechanisms influences the maturity between buyer-supplier relationships in supply chains and the generation of relational rents related to participants. The Relational View is used as theoretical lens of this study which used mixed methods by two phases. The qualitative phase was carried out through case studies, that analyzed the phenomenon within the context of organic foods supply chains and the use of governance mechanisms during buyer-supplier relationships’ maturity phases in order to generate relational rents. The quantitative data in the second phase of this study consisted of a survey with 181 organic producers in Brazil. The purpose of this phase was verify the relationship between the governance mechanisms and the generation of relational rents integrating the results from the qualitative data analysis. The results confirmed that the complementary use of governance mechanisms influences the generation of relational rents and the continuity of the relationships. Contextual factors, relationship length, power asymmetry and demand uncertainty have not shown an influence on the governance mechanisms for the generation of relational rents. On the other hand, the incentive in the use of informal mechanisms by the practices of the buying companies, such as inter-firm social enforcement and culture sharing have been shown to be important for the expansion of these gains. Nevertheless, the diminishing power asymmetry by the part of the buying company can allow a governance based on greater use of informal mechanisms. This generates relational rents and value in relationships by differentiating them from competing dyads. Theoretically, this study contributes to the assumptions of the dynamic model of the Relational View, which identifies that despite the initial motivations related to the complementarity of resources in the dyads, the maturity of relationships demands the use of governance mechanisms and internal factors to the organizations. Evidences have shown that the level of maturity of interorganizational relationships may evolve, but may also regress. As a managerial contribution, the study shows that when the buying company is able to maintain complementarity in the use of mechanisms, it also encourages the use of informal mechanisms, relationships become more resilient to adverse events, relational inertia is minimized, or even avoided, and, consequently, the greater are the relational rents. By shifting the focus of technical and transactional aspects to emphasizing the valuation of suppliers, the buying company can help in mutuality, that is, in the harmony of the expectations of the members, guaranteeing the continuity of relationships and avoiding the regression of maturity phases. Socially, the study contributes to enhancing the role of the organic farmer and making it possible, through evidence, to reflect public and business leaders on the sector's difficulties. In addition, to seeking alternatives to overcome them in order to increase and disseminate organic production, not only through transactions of an economic nature, but based on relationships.
Keywords: Relacionamentos interorganizacionais (RIOs); Mecanismos de governança; Maturidade do relacionamento; Ganhos relacionais; Setor de alimentos orgânicos; Interorganizational relationships (IORs); Governance mechanisms; Maturity of the relationship; Relational rent; Organic food industry; ACCNPQ::Ciências Sociais Aplicadas::Administração